A gas tension device for the mesopelagic zone. (September 2018) - Reed, Andrew; McNeil, Craig; D'Asaro, Eric; Altabet, Mark; Bourbonnais, Annie; Johnson, Bruce
Abstract: Gas Tension Devices (GTDs) are used to acquire accurate and stable measurements of gas tension, or total dissolved air pressure of the gases dissolved in water. GTDs operate by measuring the barometric pressure of a small sample volume of air separated from the water by a gas-permeable membrane resting on a rigid permeable support. Existing GTDs use a compressible polydimethylsiloxane (PDMS) membrane which exhibit several undesirable features: the membrane collapses with increasing hydrostatic pressure, which reduces the permeability; a collapsed membrane increases the response; collapse and expansion generate large transient signals [McNeil et al. 2006a]. Also, reverse osmosis becomes a problem at depths greater than approximately 330 m in seawater. We present a new GTD that solves the hydrostatic pressure-generated transients and changing response times, and alleviates reverse-osmosis. These improvements allow the new GTD to be used in the mesopelagic zone. The new GTD uses a custom designed small diameter (4 cm) thin (130 µm) incompressible composite Teflon-AF 2400 membrane. It can operate to a depth of at least 1000 m with a depth-independent response time of approximately 35 min. We estimated the hydrostatic pressure dependence of Henry's Law solubilities as we characterized the new Teflon-membrane GTD using data collected in the laboratory. Field testing occurred on two APL/UW Gas-Profiling Floats deployed in the Eastern Tropical North Pacific (ETNP) for 15 days during May 2014. The floats profiled between the surface and 400 m depth, sampling gas tension within the Oxygen Deficient Zone. The gas tension-profiles from the two GTDs were validated against gas tension derived from independent N2 :Ar and Ar concentrations measured by mass spectrometry, agreeing to within ± 0.6% and ± 0.4%. Highlights: A new gas tension device (GTD) improves on previous designs of GTDs. The new GTD can operate up to 1000 m depth with no pressure dependency. Two GTDs successfully measured total dissolved gases in an Oxygen Minimum Zone. The GTDs were accurate to ± 0.6% compared with independent dissolved gas data.